Gold Kiwi-Derived Nanovesicles Mitigate Ultraviolet-Induced Photoaging and Enhance Osteogenic Differentiation in Bone Marrow Mesenchymal Stem Cells - Doyeon Kim; Chanho Lee; Manho Kim; Ju Hyun Park (Antioxidants)
Bone marrow mesenchymal stem cells (BM-MSCs) play a crucial role in bone formation through their ability to differentiate into osteoblasts. Aging, however, detrimentally affects the differentiation and proliferation capacities of BM-MSCs, consequently impairing bone regeneration. Thus, mitigating the aging effects on BM-MSCs is vital for addressing bone-related pathologies. In this study, we demonstrate that extracellular nanovesicles isolated from gold kiwi (GK-NVs) protect human BM-MSCs from ultraviolet (UV)-induced photoaging, thereby alleviating aging-related impairments in cellular functions that are crucial for bone homeostasis. Notably, GK-NVs were efficiently taken up by BM-MSCs without causing cytotoxicity. GK-NVs reduced intracellular reactive oxygen species (ROS) levels upon UV irradiation, restoring impaired proliferation and migration capabilities. Furthermore, GK-NVs corrected the skewed differentiation capacities of UV-irradiated BM-MSCs by enhancing osteoblast differentiation, as evidenced by the increased expression in osteoblast-specific genes and the calcium deposition, and by reducing adipocyte differentiation, as indicated by the decreased lipid droplet formation. These findings position GK-NVs as a promising biomaterial for the treatment of bone-related diseases such as osteoporosis.